Encoding Gene Identification in Staphylococcus aureus enterotoxin B from Nasal Mucosa of the Dog - Arifah, Sitti; Effendi, Mustofa Helmi; Sektiari, Bambang (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2020)
This research aimed to know the enterotoxin B in Staphylococcus aureus isolated from the nasal mucosa of the dog. Six of fifteen samples have characteristics like cocci shaped, Gram-positive, mannitol fermented, produce catalase, coagulase and acetyl methyl carbinol. Then to identify enterotoxin B in 6 isolates of Staphylococcus aureus using PCR techniques. Result of the identification of gene that are 50% positive samples had enterotoxin B. Further research is needed on high sensitivity antibiotic for treatment of the caused by Staphylococcus aureus infections, as well as the need cautious to the spread of enterotoxin B in Staphylococcus aureus.Â